2007
DOI: 10.1002/chem.200701035
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Nickel‐Catalyzed Cross‐Coupling Reactions of Trialkynylindium Reagents with Racemic Secondary Benzyl Bromides

Abstract: The first enantioselective sp-sp3 cross-coupling reaction between alkynyl organometals and racemic benzyl bromides is reported. The coupling is performed at room temperature by using NiBr2diglyme and (S)-(iPr)-Pybox as the catalytic system and trialkynylindium reagents as nucleophiles. The reaction is stereoconvergent, both enantiomers of the racemic benzyl bromide are converted into one enantiomer of the product, and stereospecific. The reaction takes place efficiently in good yields and with high atom econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(46 citation statements)
references
References 41 publications
(16 reference statements)
1
44
0
1
Order By: Relevance
“…In β-alkyl-substituted 1,1-dibromoalkenes, trans-selective monosubstitution can be satisfactorily performed by using different nucleophiles; but when an aryl group is placed at the β-position, the disubstitution reaction becomes an important side-reaction. In our case, we observed that the reaction of triphenylindium (40 mol-%) with 1,1-dibromonon-1-ene (15; 4 ] or [Pd(dppf)Cl 2 ] as the catalyst resulted in the formation of the dicoupling product as the major one. Careful examination of different palladium complexes and reaction conditions led to the discovery that the best results for the monocoupling reaction with R 3 In were obtained with [Pd 2 dba 3 ] and P(2-furyl) 3 (1:1, 2 mol-%) as the catalyst system at 0°C for 8-10 h. Under these conditions, the reaction of Ph 3 In with 15 afforded the monocoupling product 22 in 55 % yield accompanied by 18 % of the dicoupling product (Table 4, Entry 1).…”
Section: Palladium-catalysed Cross-coupling Reactions Of R 3 In With mentioning
confidence: 85%
See 2 more Smart Citations
“…In β-alkyl-substituted 1,1-dibromoalkenes, trans-selective monosubstitution can be satisfactorily performed by using different nucleophiles; but when an aryl group is placed at the β-position, the disubstitution reaction becomes an important side-reaction. In our case, we observed that the reaction of triphenylindium (40 mol-%) with 1,1-dibromonon-1-ene (15; 4 ] or [Pd(dppf)Cl 2 ] as the catalyst resulted in the formation of the dicoupling product as the major one. Careful examination of different palladium complexes and reaction conditions led to the discovery that the best results for the monocoupling reaction with R 3 In were obtained with [Pd 2 dba 3 ] and P(2-furyl) 3 (1:1, 2 mol-%) as the catalyst system at 0°C for 8-10 h. Under these conditions, the reaction of Ph 3 In with 15 afforded the monocoupling product 22 in 55 % yield accompanied by 18 % of the dicoupling product (Table 4, Entry 1).…”
Section: Palladium-catalysed Cross-coupling Reactions Of R 3 In With mentioning
confidence: 85%
“…[7,24] 1,1-Dibromo-1-alkenes were prepared from their corresponding aldehydes according to the method of Corey and Fuchs. [8b,25] [Pd(Ph 3 P) 4 ] [26] and [Pd(DPEphos)Cl 2 ] [19] were prepared according to literature procedures. All other commercially available reagents were used as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was performed in a 1:1 mixture of DMA and THF at room temperature with 10 % NiBr 2 ·diglyme and 13 % (S)-iPr-Pybox loadings, affording the products in 77-87 % ee and yields of 30-70 %. [42] Gagné and co-workers reported the coupling of glycosyl halides with alkyl-and arylzinc reagents by using NiCl 2 -Pybox (44, R = H) as the catalyst. [43] Lin et al suggested a Ni I -Ni III mechanism for the reaction of racemic secondary alkyl electrophiles on the basis of a DFT calculation study.…”
Section: Negishi Reactionsmentioning
confidence: 99%
“…A distinct chemoselectivity of triorganoindium reagents has been observed favoring replacement of bromo over chloro functionalities in 2,5-dihalopyrimidines [360]. The chemistry of alkynylindium reagents has recently been extended to metalcatalyzed enantioselective C(sp)-C(sp 3 ) cross-couplings [363]. Racemic secondary benzyl bromides 134 reacted with trialkynylindium reagents under Ni catalysis in the presence of the chiral ligand 135.…”
Section: Alkynylindium Reagentsmentioning
confidence: 99%